A new permanent multi-parameter monitoring network in Central Asian high mountains – from measurements to data bases - T. Schöne; C. Zech; K. Unger-Shayesteh; V. Rudenko; H. Thoss; H.-U. Wetzel; A. Gafurov; J. Illigner; A. Zubovich (Geoscientific Instrumentation, Methods and Data Systems, 2013)
Long-term monitoring of water resources and climate parameters at the scale of river basins requires networks of continuously operated in-situ stations. Since 2009, GFZ and CAIAG, in cooperation with the National Hydrometeorological Services (NHMS) of Central Asia, are establishing such a regional monitoring network in Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan, and lately Afghanistan to collect observations of meteorological and hydrological parameters and to deliver them to the end-users for operational tasks and scientific studies. The newly developed and installed remotely operated multi-parameter stations (ROMPS) do not only monitor standard meteorological and hydrological parameters, but also deliver Global Navigation Satellite System (GNSS) data for atmospheric sounding as well as tectonic studies. Additionally, three stations integrate seismic sensors for earthquake monitoring. The observational data from the ROMPS is transmitted nominally in near-real time, but at least once a day to a centralized geo-database infrastructure for long-term storage and data redistribution. Users can access the data manually using a web-interface or automatically using SOS requests; in addition, data is planed to be distributed to the NHMS through standard communication and data exchange channels.